Penggunaan Elemen Visual Dalam Membangun Identitas Brand Pada Konten Media Sosial Instagram Produk Kopi Kutjur Kabupaten Pasuruan - Nabila Cessarila Prassiwi; Widyasari Widyasari; Aditya Rahman Yani (UNIVERSITAS STEKOM, 2026)
Social media is a platform for obtaining information, entertainment, and real-time communication. One of the platforms widely used in business activities is Instagram due to its ease of use and effectiveness as a promotional medium. However, the use of social media needs to be supported by appropriate visual element management to attract attention and build consumer trust. This study aims to analyze the relationship between visual elements in content, brand identity formation, and their influence on consumer perception. The method used is qualitative, involving observation, interviews, and questionnaires distributed to 124 respondents. The results show that before the redesign, Kopi Kutjur's content lacked visual consistency. After implementing consistent visual elements such as color palette, typography, supergraphics, and layout, the content becomes more structured and develops a clearer brand identity. Keywords: Instagram, Visual Elements , Brand Identity, Digital Promotion, Local Cofee